Penerapan Model Pembelajaran TPS Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Virus - Luis Sandi Najoan; Helen J. Lawalata; Mariana Rengkuan (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The Think Pair Share cooperative learning technique is highly effective in fostering diverse discussion patterns. The purpose of Think Pair Share learning is to shape student interaction habits. The Think Pair Share instructional approach provides students with extended opportunities for reflection, articulation, and collaborative assistance. The objective of this study is to enhance the academic performance of students in class X viral material at SMA Negeri 2 Tondano by applying the Think Pair Share instructional approach. The research methodology employed is known as Classroom Action Research (PTK), which is conducted in two cycles, with each cycle comprising four distinct stages: preparation, implementation/action, observation, and reflection. The research findings indicate that the implementation of the Think Pair Share (TPS) instructional approach has resulted in a significant enhancement of student learning outcomes in class 86.66% during cycle II. This indicates that the research findings have met the success criterion, specifically, that at least 75% of students have successfully finished.